2010
DOI: 10.35808/ersj/291
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual Capital and Business Performance: An Empirical Study for the Greek Listed Companies

Abstract: The aim of this study is to empirically examine the four elements of intellectual capital (human capital, customer capital, structural capital and innovation capital) and their relationship with business performance in the Athens Stock Exchange (ASE). This study was conducted based on a psychometrically validated questionnaire developed and launched by Bontis (1997) and Bontis et al. (2000). Confirmatory Factor Analysis and Structural Equation Model have been used as statistical methods to analyse the five hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 22 publications
2
36
0
4
Order By: Relevance
“…Similarly, Maditinos, Šević and Tsairidis [20] affirm that once enterprises properly use the organizational body of knowledge, they will gain a sustainable competitive edge which will later result in business performance. A pertinent usage of the structural capital would ensure the formation of knowledge-intensive groups performing higher tasks [4,26].…”
Section: Research Directions Bridging Intellectual Capital and Smes Imentioning
confidence: 96%
“…Similarly, Maditinos, Šević and Tsairidis [20] affirm that once enterprises properly use the organizational body of knowledge, they will gain a sustainable competitive edge which will later result in business performance. A pertinent usage of the structural capital would ensure the formation of knowledge-intensive groups performing higher tasks [4,26].…”
Section: Research Directions Bridging Intellectual Capital and Smes Imentioning
confidence: 96%
“…They found a strong, positive relationship and concluded that the companies in the sample manage intellectual capital effectively and this contributes their performance positively. Maditinos et al (2010) mention about the four elements of intellectual capital as human, customer, structural and innovation capital and they tested the inter-relationships among the elements and the relationship with business performance. They applied a psychometrically validated questionnaire to the sample composed of companies from Athens Stock Exchange and grouped as service and non-service.…”
Section: Review Of Literaturementioning
confidence: 99%
“…This indicates that when investor will invest, they will not use regular stock capital as rate to discount dividend expected to be accepted in the future. According to Byun, Kwak, & Hwang (2008) (Byun, Kwak, & Hwang, 2008;Fairfield, Whisenant, & Yohn, 2003;Maditinos, Šević, & Tsairidis, 2010;Mohamad & Saad, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…There is negative influence of relational capital towards cost of equity capital not stated as valid. Further, (Chen, Cheng, & Hwang, 2005;Maditinos, Šević, & Tsairidis, 2010;Mangena et al, 2011) concluded that the larger the corporation reveal intellectual capital in yearly report, the lower the equity cost is. It is because the investors find useful information to assess the company.…”
Section: Page3mentioning
confidence: 99%